De las guerras de religión a las políticas en el Eusebio de Montengón: la tolerancia y el humanitarismo - Chen Sham, Jorge (2015)
The limits of religious tolerance towards human respect and goodwill are questioned in the Bildungsroman, or comingof- age novel. Young Eusebio must learn the lessons during his journey through British soil in the eponymous novel, where he observes the ravages and excesses of the wars of religion and ponders their impact when human heart and mind degenerate, because men follow their passions with the violence/anger of a “ferocious animal”. This discussion is based on the arguments philosophers like Locke, Hume, and Voltaire make regarding religious wars and the lack of tolerance that happens in these cases against those who practice a different religion.